2020
DOI: 10.1155/2020/4910601
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase‐1 Suppresses Wnt Signaling Pathway in Nonalcoholic Steatohepatitis‐Related Liver Fibrosis

Abstract: Background and Aim. Heme oxygenase-1 (HO-1) has been verified to play an important role in nonalcoholic steatohepatitis (NASH), but the mechanism remains unclear. In this study, we aimed to clarify whether induction of HO-1 reverses steatofibrosis via suppression of the Wnt signaling pathway and to explore the potential mechanism of HO-1 on NASH-related liver fibrosis. Methods. Mice were fed with a methionine-choline-deficient (MCD) diet for 8 weeks to induce steatohepatitis-related liver fibrosis and were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Heme oxygenase-1 (HO-1), as a rate-limiting enzyme, degrades the heme into iron, biliverdin, and carbon monoxide, which share antioxidative, anti-inflammatory, and antiapoptotic activities [ 5 ]. Increasing evidence supports that HO-1 can protect liver cells from damage caused by multiple causes, such as acute liver injury and liver transplantation [ 6 ]. Studies have shown that the HO-1 promoter region contains binding sites of NF- κ B; therefore, HO-1 activity is directly related to NF- κ B [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heme oxygenase-1 (HO-1), as a rate-limiting enzyme, degrades the heme into iron, biliverdin, and carbon monoxide, which share antioxidative, anti-inflammatory, and antiapoptotic activities [ 5 ]. Increasing evidence supports that HO-1 can protect liver cells from damage caused by multiple causes, such as acute liver injury and liver transplantation [ 6 ]. Studies have shown that the HO-1 promoter region contains binding sites of NF- κ B; therefore, HO-1 activity is directly related to NF- κ B [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, Du et al, have endeavored to investigate the relationship between HO-1 and nonalcoholic fatty liver disease (NAFLD) and demonstrated that the induction of HO-1 could eliminate steatohepatitis and hepatic fibrosis in the progression of NAFLD [ 6 ], thus substantiating a significant role of HO-1 against heme-mediated steatohepatitis-related liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 also has a role in NASH pathogenesis. Recently, it was found that the administration of the HO-1 inducer hemin significantly ameliorates the severity of steatosis, inflammation, and fibrosis and also decreases the serum ALT and AST levels by inhibiting the activation of canonical and noncanonical Wnt signaling pathways in MCD mice [ 57 ]. Furthermore, a dramatic decrease in hepatic ROS, in association with a reduction in endoplasmic reticulum stress, was observed in mice fed with an MCD diet when treated with hemin [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barikbin et al investigated the effects of HO-1 induction in Mdr2-knockout mice [ 34 ]; they found that the administration of CoPP effectively suppressed liver inflammation and fibrosis in the genetic animal model of chronic liver disease [ 34 ]. Recent studies have also shown that inflammatory and fibrotic changes in fatty liver disease were effectively attenuated by HO-1 induction [ 35 , 36 ]. In addition, pharmacological or genetic induction of HO-1 suppressed carbon-tetrachloride-induced liver fibrosis in rodents [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%